Incidence, predictors and clinical characteristics of orolingual angio-oedema complicating thrombolysis with tissue plasminogen activator for ischaemic stroke. Issue 5 (12th July 2014) - Hurford, Robert; Rezvani, Sean; Kreimei, Mohammad; Herbert, Annie; Vail, Andy; Parry-Jones, Adrian R; Douglass, Chris; Molloy, Jane; Alachkar, Hana; Tyrrell, Pippa J; Smith, Craig J
Abstract : Background: Orolingual angio-oedema is a recognised complication of tissue plasminogen activator (tPA) for ischaemic stroke. We investigated its incidence, clinical characteristics and relationship with other factors in patients receiving tPA at a UK centre. Methods: 530 consecutive patients (median age 70 years) receiving tPA treatment for confirmed ischaemic stroke were included. Cases were defined as those developing angio-oedema within 24 h of initiation of tPA. Angio-oedema was retrospectively classified as mild, moderate or severe using predefined criteria. The primary analysis was the association between prior ACE inhibitor (ACE-I) treatment and angio-oedema. Results: Orolingual angio-oedema was observed in 42 patients (7.9%; 95% CI 5.5% to 10.6%), ranging from 5 to 189 min after initiation of tPA (median 65 min). 12% of the angio-oedema cases were severe (1% of all patients treated with tPA), requiring urgent advanced airway management. 172 patients (33%) were taking ACE-I. In multifactorial analyses, only prior ACE-I treatment remained a significant independent predictor of angio-oedema (odds ratio (OR) 2.3; 95% CI 1.1 to 4.7). Conclusions: Angio-oedema occurs more frequently than previously reported and is associated with preceding ACE-I treatment. Angio-oedema may be delayed and progress to life-threatening airway compromise, which has implications for the assessment and delivery of thrombolysis.